Socio-demographic factors and body image perception are associated with BMI-for-age among children living in welfare homes in Selangor, Malaysia - A. Rahim, Nur Nabilla; Chin, Yit Siew; Sulaiman, Norhasmah (MDPI, 2019)
Considering the double burden of malnutrition in Malaysia, data on malnourished children living in welfare homes are limited. This study aimed to determine the body weight status of children living in welfare homes and its associated factors. A total of 307 children aged 7–17 years old living in 15 selected welfare homes completed a standardized questionnaire, and their body weight and height were measured by trained researchers. There were 54.4% orphans, 23.8% abandoned children, and 21.8% children from problematic families. There were 51.5% boys and 48.5% girls; 52.4% were Malays, followed by 31.3% Indians, 12.7% Chinese, and 3.6% from other ethnic groups. The prevalence of overweight and obesity (23.1%) was higher than the prevalence of thinness (8.5%). In bivariate analyses, socio-demographic factors of age (p = 0.003), sex (p = 0.0001), ethnicity (p = 0.001), and welfare home enrollment status (p = 0.003), and psychological factors of self-esteem (p = 0.003), body shape dissatisfaction (p = 0.0001), and underestimation of body weight status (p = 0.002), were significantly associated with body mass index (BMI)-for-age. In the multiple linear regression analysis, children who were either Malays (β = 0.492) or Chinese (β = 0.678), with a status of being abandoned (β = 0.409), with body shape dissatisfaction (β = 0.457), and underestimated body weight status (β = 0.628) significantly explained 39.7% of the variances in higher BMI-for-age (F = 39.550; p < 0.05). Besides socio-demographic background, the current findings emphasized the importance of incorporating body image perception in an obesity prevention intervention program in welfare homes.